Frequency modulation (FM)-frequency shift keying (FSK) receiver - 389042 Lau, Phooi Chee (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Electronicss)) - Universiti Teknologi Malaysia, 2002